Unraveling the Lipidomic Determinants of Atrial Fibrillation: An Extensive Mendelian Randomization Study - Ye, Lingyan; Lin, Dongli; Chen, Feng; Huang, Xiaoyong; Wu, Xianjun (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2026)
BackgroundAtrial Fibrillation (AF) is the most prevalent form of cardiac arrhythmia, with a complex etiology that implicates lipid metabolism. This study employs Mendelian Randomization (MR) to dissect the causal relationships between lipidomic profiles and AF, utilizing comprehensive genetic data to clarify these associations.MethodsSummary statistics for 179 lipid species across 13 classes were retrieved from the GWAS Catalog, encompassing 7,174 Finnish individuals from the GeneRISK study. For AF, data were synthesized from six major studies comprising over one million subjects. Our Two-Sample MR (TSMR) approach was implemented using Inverse Variance Weighting (IVW), MR-Egger, and MR-PRESSO for sensitivity analysis. Additionally, we uniquely integrated the Mendelian Randomization-Bayesian Model Averaging (MR_BMA) method to robustly prioritize the most likely causal lipid determinants of AF, and performed bidirectional MR analysis to assess potential reverse causality.ResultsThe TSMR analysis, reinforced by MR_BMA, revealed significant causal associations between specific lipid species and AF risk. In particular, Phosphatidylcholine (17:0_18:2) was associated with a decreased risk of AF (OR = 0.96, 95% CI 0.93–0.99, P<0.05), whereas Phosphatidylcholine (16:0_20:5) and Phosphatidylcholine (17:0_20:4) were linked to increased risks (OR = 1.04, 95% CI 1.01–1.07, P<0.01; and OR = 1.02, 95% CI 1.00–1.05, P<0.05, respectively). Furthermore, elevated levels of Phosphatidylethanolamine (18:0_20:4) (OR = 1.03, 95% CI 1.01–1.06, P<0.01) and Triacylglycerol (50:4) (OR = 1.04, 95% CI 1.00–1.07, P<0.05) were also associated with increased AF risk. In addition, Sphingomyelin (d34:2), Sterol ester (27:1/18:0), and Sterol ester (27:1/18:3) emerged as further risk factors, thereby expanding the spectrum of lipidomic determinants implicated in AF. The bidirectional MR analysis provided no evidence of reverse causation, reinforcing the directionality of the lipid-driven association. Sensitivity analyses demonstrated robust findings with no indication of pleiotropy or heterogeneity.ConclusionThis study provides strong evidence for thecausal role of specific lipid species in the development of AF. Our comprehensive MR analysis not only deepens our understanding of AF pathophysiology but also highlights the therapeutic potential of targeting these lipid alterations. Notably, the absence of reverse causation supports a unidirectional relationship wherein altered lipid species drive AF risk.
Keywords: cardiovascular genetics